Pengaruh Teknologi Pemupukan terhadap Kualitas Tanah, Pertumbuhan dan Hasil Padi Varitas Ciherang yang Ditanam pada Sawah Bukaan Baru di Dusun Kleseleon, Kabupaten Malaka, Nusa Tenggara Timur - Sukristiyonubowo Sukristiyonubowo; Damasus Riyanto; Sugeng Widodo (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2019)
Sukristiyonubowo et al, 2019. The Influence of Fertilizer Technologies on Soil Quality, Rice Growth and Biomass Production of Ciherang Vareity Cultivated in Newly Developed Lowland Rice Fields of Kleseleon, Malaka District. JLSO 8(1):1-10.Highly weathered and potential acid sulphate soils are granted for newly developed lowland rice. They have many short comings including low in major elements and Fe and Mn in toxic levels. Study on soil fertility, rice growth and biomass productions of Ciherang variety planted in newly developed lowland rice was conducted in Kleseleon Village, Malaka District in 2014. The aim of study was to know the effect of technologies on soil fertility properties, rice growth and biomass productions.The experiment was started in February 2014 and harvested in June 2014. Five promising treatments were studied including: Farmers Practices, Package A : NPK recommended rate + 3 tons compost, Package B : NPK recommended rate + 2 tons compost + Bio fertilizer, Package C: ¾ recommended rate + 3 tons compost + Bio fertilizer and Package D: NPK recommended rate + 2 tons compost + Bio fertilizer, in which N, P and K were split two times: 50 % given at planting time and 50 % at 21 DAP. Two kilo gram composite soils from five points and ring samples of 0-20 cm in depth were taken in February 2014 for analyzing chemical, physical and biological parameters, before soil ploughing. The results indicated that the soil quality of newly developed low land rice fields in Kleseleon was low. These technologies increased the soil fertility including soil pH, soil organic C, available P and K extracted with HCl 25 %. In addition, the best technology was observed in package B (NPK Recommendation rate + 2 tons organic fertilizer + Bio fertilizer/SMART, in which N and K fertilizer were applied 3 times: 50 % at planting, 25 % at 21 HST and 25% before flowering) for tillers number and rice biomass productions. The yield reached 5.88 ± 0.29 and 4.84 ± 0.47 tons ha-1 season-1 for rice grains and rice straw, respectively.